Mechanisms underlying the effects of nitrogen and phosphorus on the growth and berberine biosynthesis of Phellodendron chinense Schneid - Yang, Le; Gu, Yuanzheng; He, Hanjie; Wang, Guangjun; Qadri, Rashad; Yan, Wende; He, Gongxiu; Zhou, Rui (Frontiers in Plant Science, 2025)
IntroductionPhellodendron chinense Schneid (P. chinense Schneid) is a woody medicinal herb valued for its production of the bioactive compound berberine. Both its growth and berberine biosynthesis are regulated by nitrogen (N) and phosphorus (P) availabilities. However, the role of N and P in regulating rhizosphere soil, microenvironments, and microbial interactions remains unclear.MethodsTo investigate regulatory effects of N and P on P. chinense Schneid seedlings, a seedbed experiment was conducted using five nutrient treatments: a control (CK), N alone (N10), and N combined with three levels of P (N10P5, N10P10, and N10P15). This study assessed changes such as pH, SOM, TN, and TP in soil properties, microbial communities, soil enzyme activities, plant biomass, berberine content, gene expression profiles, and metabolite content.ResultsExperimental results demonstrated that, compared to the N10 treatment, combined N and P addition (N10P5, N10P10, and N10P15) significantly reduced the soil pH, soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), available phosphorus (AP) and potassium (AK), and bacterial α-diversity, suppressed the enzymatic activities in carbon and nitrogen metabolisms, whereas significantly increased the relative abundance of microbial taxa in the soil of P. chinense Schneid seedlings. Additionally, the combined treatments, especially N10P10 increased plant height by 83.80%, biomass by 82.07%, and berberine content by 13.57%. Correspondingly, expression analysis revealed that 5 metabolites including estrone and N-acetyl-L-leucine, etc., as well as the expression of 8 genes (e.g., gdhA, smtA, and sga) were upregulated in soil of P. chinense Schneid seedlings.DiscussionThis study revealed a novel rhizosphere-mediated mechanism for N/P interaction in medicinal plants. We have found that N10P10 level significantly changes the soil microenvironment. These changes were related to the alterations in key functional gene expression and metabolic profiles, which promoted biomass growth and enhanced berberine synthesis in P. chinense Schneid seedlings. Therefore, it provides a concrete agronomic strategy: applying a balanced N:P ratio of 10:10 can be recommended to simultaneously maximize both the biomass and medicinal quality of P. chinense Schneid in cultivation.